Effect of period of weed interference on growth and yield of soybean (Glycine max L. Merrill) - Daramola, Olumide Samuel; Adeyemi, Olusegun Rapheal; Adigun, Joseph Aremu; Adejuyigbe, Christopher Olu (Journal of Agricultural Sciences (Belgrade), 2020)
Field trials were conducted to evaluate the effect of different periods of weed interference on weed infestation, growth and yield of soybean during 2016-2017 cropping seasons. In both years, soybean grain yields ranged from 888-1148 kg ha -1 in plots where weeds were allowed to grow till harvest to 2103-2389 kg ha -1 in plots where weeds were controlled till harvest, indicating a 52-58% yield loss with uncontrolled weed growth. Weed interference until 3 weeks after sowing (WAS) had no detrimental effect on soybean growth and yield provided the weeds were subsequently removed. However, further delay in weed removal until 6 WAS or longer depressed soybean growth and resulted in irrevocable yield reduction, with number of pods per plant being the most affected yield component. For optimum growth and yield, it was only necessary to keep the crop weed-free between 3 and 6 WAS.